2007
DOI: 10.1111/j.1537-2995.2007.01235.x
|View full text |Cite
|
Sign up to set email alerts
|

Frequent detection of the parvoviruses, PARV4 and PARV5, in plasma from blood donors and symptomatic individuals

Abstract: PARV4 and PARV5 are readily detected in manufacturing plasma pools, test pools (constructed from 16 donations), and individual donations derived from healthy blood donors. The prevalence of these viruses was increased in plasma samples from febrile patients. Despite the use of highly sensitive assays for HBoV, it was not possible to identify manufacturing plasma pools containing HBoV sequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
145
2
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(167 citation statements)
references
References 21 publications
(33 reference statements)
18
145
2
2
Order By: Relevance
“…So far, the virus has been isolated from many tissues including bone marrow of HIV-positive individuals (13) and the liver of HBVand HCV-infected patients (14,15). Moreover, the virus has been diagnosed in plasma, cerebrospinal fluid (CSF), skin, myocardium, and blood products around the world (1,3,7,8,11,(15)(16)(17). Despite the detection of viral nucleic acid in many organs, PARV4 has scarcely been linked to specific symptoms, except for a recent study that was conducted in Africa linking PARV4 to encephalitis (11) and another study in which the virus was diagnosed in people with symptoms including pharyngitis, nausea, and joint pain (1).…”
Section: Introductionmentioning
confidence: 99%
“…So far, the virus has been isolated from many tissues including bone marrow of HIV-positive individuals (13) and the liver of HBVand HCV-infected patients (14,15). Moreover, the virus has been diagnosed in plasma, cerebrospinal fluid (CSF), skin, myocardium, and blood products around the world (1,3,7,8,11,(15)(16)(17). Despite the detection of viral nucleic acid in many organs, PARV4 has scarcely been linked to specific symptoms, except for a recent study that was conducted in Africa linking PARV4 to encephalitis (11) and another study in which the virus was diagnosed in people with symptoms including pharyngitis, nausea, and joint pain (1).…”
Section: Introductionmentioning
confidence: 99%
“…PARV4 is not closely related to any other parvovirus described to date, and may constitute a new group within the parvovirus family. Detection of PARV4 infections has to date been restricted to pooled plasma or plasma-derived blood products (Fryer et al, 2006(Fryer et al, , 2007b and to autopsy samples of lymphoid tissue, bone marrow or liver from study subjects in the USA and Europe Simmonds et al, 2007;Longhi et al, 2007;Fryer et al, 2007d;Schneider et al, 2008). Compared with other parvoviruses, which are predominantly transmitted through respiratory routes, PARV4 infections show an unusual risk-group association.…”
mentioning
confidence: 99%
“…The fi rst prevalence studies, performed mainly in North America and the United Kingdom, reported fi nding the virus in plasma samples from febrile patients who had symptoms resembling those of acute HIV infection (6%), from cadavers of hepatitis C RNA-positive intravenous drug users (30%), and in plasma donations from healthy blood donors (5% pooled, 2% individual) (3)(4)(5). PARV4 was also identifi ed in clotting factor VIII concentrate and in plasma pools negative for parvovirus B19 DNA (5,6).…”
mentioning
confidence: 99%
“…PARV4 was also identifi ed in clotting factor VIII concentrate and in plasma pools negative for parvovirus B19 DNA (5,6). This new virus appears to not be restricted solely to blood samples; it has been already identifi ed in bone marrow, in various autopsy tissue samples from patients with AIDS, and in liver tissues of persons with liver dysfunctions (7)(8)(9).…”
mentioning
confidence: 99%